Efficacy Comparison of Nitazoxanide Combined with Lactulose versus Lactulose Monotherapy in Managing Overt Hepatic Encephalopathy - Taimoor Hafeez Janjua; Amanat Ali; Sameer Ahmed; Sabeen Shakir; Zunera Rashid; Asma Irfan (Journal of Rawalpindi Medical College)
Objective: To evaluate the efficacy of combining Nitazoxanide with lactulose compared to lactulose alone in the treatment of overt hepatic encephalopathy.